2023
DOI: 10.1371/journal.pbio.3002416
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and scalable genome-wide essentiality mapping to identify nonessential genes in phages

Denish Piya,
Nicholas Nolan,
Madeline L. Moore
et al.

Abstract: Phages are one of the key ecological drivers of microbial community dynamics, function, and evolution. Despite their importance in bacterial ecology and evolutionary processes, phage genes are poorly characterized, hampering their usage in a variety of biotechnological applications. Methods to characterize such genes, even those critical to the phage life cycle, are labor intensive and are generally phage specific. Here, we develop a systematic gene essentiality mapping method scalable to new phage–host combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 135 publications
0
8
0
Order By: Relevance
“…On a dataset of 56 whole-genome essentiality studies in bacteria from the DEG database (Zhang, 2004) and two whole-genome essentiality studies in phage from Piya et al (2023), we observed that the changes in Evo log-likelihood with 66k context are significantly predictive (Bonferroni-corrected permutation-based P < 0.05) of gene essentiality in 43 out of 58 genomes. We also observed that providing the model with additional genomic context beyond the gene sequence results in a substantial improvement in performance, especially from gene only context to 8k context.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…On a dataset of 56 whole-genome essentiality studies in bacteria from the DEG database (Zhang, 2004) and two whole-genome essentiality studies in phage from Piya et al (2023), we observed that the changes in Evo log-likelihood with 66k context are significantly predictive (Bonferroni-corrected permutation-based P < 0.05) of gene essentiality in 43 out of 58 genomes. We also observed that providing the model with additional genomic context beyond the gene sequence results in a substantial improvement in performance, especially from gene only context to 8k context.…”
Section: Resultsmentioning
confidence: 95%
“…With 8k context, the model most likely has access to enough of the genome to improve its prediction of mutational effects on organism function, whereas 66k context provides new, helpful information in only some cases. For a few genomes, the zero-shot performance with 66k context is notably strong, with an AUROC of 0.86 on lambda phage essentiality data (Piya et al, 2023) and an AUROC of 0.81 on Pseudomonas aeruginosa essentiality data (Turner et al, 2015) ( Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One mechanism by which phages have evolved a non-integrative lysogenic state is through the acquisition of plasmid genes. Phage-plasmids (PPs) are large DNA elements (larger than phage or plasmid alone, >90Kb), that encode phage, plasmid, and accessory genes 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism by which phages have evolved a non-integrative lysogenic state is through the acquisition of plasmid genes. Phage-plasmids (PPs) are large DNA elements (larger than phage or plasmid alone, >90Kb), that encode phage, plasmid, and accessory genes 22,23 . Rather than switching between lysis and integration, PPs switch between phage lysis and low-copy number plasmid replication modes 24 .…”
Section: Introductionmentioning
confidence: 99%